High-elastic anti-wrinkle superfine fiber sneaker surface leather

By using anionic aqueous urethane and isocyanate modified chitosan and other additives to form a cross-linked three-dimensional structure in the microfiber sports upper leather, the problems of insufficient elasticity and wrinkle resistance of existing microfiber synthetic leather are solved, and the effects of high elasticity, wrinkle resistance and acid and heat resistance are achieved.

CN119640594APending Publication Date: 2025-03-18FUJIAN ZHONGYU WATERBORNE MICROFIBER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510039929.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing microfiber synthetic leather is difficult to have the elasticity and wrinkle resistance requirements for shoes. The surface is prone to wrinkles and cracks during use, and it cannot provide comfortable wrapping performance on the feet.

Method used

A high elastic wrinkle-resistant microfiber sports upper is adopted, including a base layer, a foam layer and a top layer. The base layer is a microfiber layer, the foam layer is a PU foam layer, and the surface layer is a coating, pre-drying, load-pressurized and cured after mixing at least two anionic aqueous urethanes with additives and solvent water. The additives include crosslinking agents and isocyanate modified chitosan. By forming a mesh structure and crosslinking three-dimensional structure, the structural strength and acid and heat resistance of the surface layer are improved.

Benefits of technology

It achieves high elasticity and wrinkle resistance, high overall structural strength, good elasticity and acid and heat resistance, avoids elastic loss of the surface layer, and improves the bonding strength with the PU foam layer, and enhances the peel strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640594A_ABST
    Figure CN119640594A_ABST
Patent Text Reader

Abstract

The invention discloses high-elastic anti-wrinkle superfine fiber sneaker surface leather, which relates to the technical field of synthetic leather, and comprises a base layer, a foaming layer and a surface layer, the base layer is a superfine fiber layer, the foaming layer is a PU foaming layer, and the surface layer is formed by mixing at least two kinds of anionic water-based urethane, auxiliaries and solvent water according to the weight part ratio of (1.8-2.2): (0.05-0.5): (5-7), coating, pre-drying, attaching to the outer side of the PU foaming layer, and carrying out load pressurization and curing molding; the auxiliary agent comprises a cross-linking agent and isocyanate modified chitosan; the isocyanate modified chitosan is obtained by carrying out a cross-linking reaction on 1, 6-hexamethylene diisocyanate and chitosan. Chitosan is modified by isocyanate to form a net-shaped structure, and the net-shaped structure and the cross-linking agent cooperate with at least two anionic waterborne urethane to form a cross-linked three-dimensional structure with a compact structure, so that the effect of improving acid resistance and thermal stability is achieved while the hydrophilic capacity of the surface layer is reduced, the overall structural strength is high, good elasticity is achieved, and the service life of the surface layer is prolonged. Therefore, the anti-wrinkle purpose is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of synthetic leather, and in particular to a highly elastic and wrinkle-resistant ultrafine fiber sports shoe upper leather. Background Art

[0002] Natural leather is widely used in the production of daily necessities and industrial products due to its excellent natural properties. However, with the growth of the world's population, the demand for leather has doubled, and the limited amount of natural leather has long been unable to meet this demand. To solve this contradiction, scientists began to study and develop artificial leather and synthetic leather decades ago to make up for the shortcomings of natural leather. However, the traditional processing technology will destroy the structure of microfibers during the processing, thereby affecting the physical properties, light perception and feel of the product, and it is difficult to play a good role in improving the upper leather.

[0003] The Chinese patent application document with publication number CN118653303A discloses a superfine fiber synthetic leather and a processing method thereof, and the processing method of the superfine fiber synthetic leather comprises the following steps: nylon slices and polyethylene slices are made into blended sea island superfine fibers through a spinning process; then, a web laying, acupuncture, and heat setting process are performed to obtain a shaped non-woven fabric; thereafter, a wet extrusion impregnation treatment is performed, and a wet semi-finished bass is obtained through a coagulation and washing process; the wet semi-finished bass is opened by a benzene reduction method to obtain an opened semi-finished product; the opened semi-finished product is dried, and then oiled through an oil tank containing a three-in-one mixed liquid, the three-in-one mixed liquid comprising a fluorine-free water repellent, an anti-high temperature yellowing agent, and an anti-phenol yellowing agent; then, a stentering setting, a leather kneading, a leather grinding and other post-treatments are performed to finally obtain the superfine fiber synthetic leather.

[0004] However, the microfiber synthetic leather obtained by the processing method of the microfiber synthetic leather is difficult to meet the elasticity and wrinkle resistance requirements for shoes. During continuous use, the microfiber synthetic leather is very likely to produce wrinkles and cracks on the surface when used in shoes, and it cannot provide comfortable wrapping performance for the feet, which needs to be improved. Summary of the invention

[0005] In view of this, the purpose of this application is to provide a highly elastic and wrinkle-resistant microfiber sports shoe upper leather to achieve the purpose of high elasticity and wrinkle resistance. The specific scheme is as follows:

[0006] A highly elastic and wrinkle-resistant microfiber sports shoe upper comprises a base layer, a foaming layer and a surface layer; the base layer is a microfiber layer, the foaming layer is a PU foaming layer, the surface layer is prepared by mixing at least two anionic water-based urethanes with an auxiliary agent and solvent water in a weight ratio of 1.8-2.2:0.05-0.5:5-7, coating and pre-drying, and then adhering to the outer side of the PU foaming layer, and then subjected to load pressurization and curing molding; the auxiliary agent comprises a crosslinking agent and isocyanate-modified chitosan; the isocyanate-modified chitosan is obtained by crosslinking reaction between 1,6-hexamethylene diisocyanate and chitosan.

[0007] Preferably, the cross-linking agent is methoxy melamine, ethoxy melamine or butoxy melamine, and the mass ratio of the cross-linking agent to the anionic water-based urethane is 0.03-0.4:1.8-2.2.

[0008] Preferably: the preparation steps of the isocyanate-modified chitosan include: ① dissolving chitosan in an organic solvent to obtain a chitosan solution with a concentration of not less than 0.2 g / ml; ② adding 1,6-hexamethylene diisocyanate solution to the chitosan solution, controlling the molar ratio of 1,6-hexamethylene diisocyanate to chitosan to be 1:4-6, and adding a catalyst to stir to obtain a mixture; ③ placing the mixture in a water bath and stirring and reflux treatment to obtain isocyanate-modified chitosan.

[0009] Preferably, the temperature of the water bath is controlled at 50-75° C., and the reflux treatment is performed for 2-12 hours.

[0010] Preferably: the catalyst is dibutyltin dilaurate.

[0011] Preferably: the two anionic water-based urethanes include COADD SC-2D-400 acrylic acid modified anionic water-based urethane oil purchased from Qieke New Material Technology (Shanghai) Co., Ltd. and water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd. in a mass ratio of 1:0.8-1.2.

[0012] Preferably: the pre-drying is to control the drying degree to 40-60%, and the load pressurization is to control the pressure to 6-22kg / cm 2 , and the curing molding is thermal curing or UV curing.

[0013] Preferably, the ultrafine fiber layer is water-soluble polyester and polyester or polyamide sea-island fiber cloth.

[0014] Preferably, the PU foam layer is composed of water-based foaming resin, copper chloride, sodium alginate in a weight ratio of 100:4-6:0.1-0.5 and hollow glass microspheres in a mass percentage of 0.85-1.12%, and the PU foam layer is obtained by mixing, coating and drying.

[0015] Preferably: the water-based foaming resin is an anionic aliphatic polyether polyurethane dispersion purchased from Wanhua Chemical 1630B.

[0016] It can be seen from the above scheme that the present application provides a high-elasticity and wrinkle-resistant microfiber sports shoe upper leather, which forms a network structure through isocyanate-modified chitosan, and cooperates with at least two anionic water-based amino acids as a cross-linking agent to form a densely structured cross-linked three-dimensional structure, thereby reducing the hydrophilicity of the surface layer while achieving the effect of improving acid resistance and thermal stability, and the overall structural strength is high and has good elasticity to achieve the purpose of wrinkle resistance.

[0017] Among them, after the composite film of at least two anionic water-based urethanes and the crosslinking agent and the isocyanate-modified chitosan is formed, the structural strength of the surface is significantly improved while reducing the loss of elasticity of the surface layer, and at the same time has the effect of improving thermal stability and acid resistance;

[0018] At the same time, the viscosity of the PU foaming layer is improved by sodium alginate, and the hollow glass microspheres are foamed into holes, while the holes are kept evenly distributed and the pore size differences are reduced during the molding process. Cupric chloride is fully dispersed in the PU foaming layer as an inorganic filler. While improving the strength of the PU foaming layer, it also improves the bonding strength with the surface layer, so as to achieve the effect of improving the peeling strength of the high-elastic and wrinkle-resistant microfiber sports shoe upper leather. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0020] Figure 1 This is a schematic structural diagram of the high-elasticity and wrinkle-resistant microfiber sports shoe upper leather disclosed in this application.

[0021] Explanation of reference numerals: 1. base layer; 2. foaming layer; 3. surface layer. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0023] It should be mentioned that the organic solvent used to dissolve chitosan in the embodiment of the present application does not react with 1,6-hexamethylene diisocyanate, for example, existing organic solvents such as dioxane are used, which will not be repeated here. In the 1,6-hexamethylene diisocyanate solution, conventional reagents such as toluene, xylene, cyclohexanone, etc. can be used as solvents, which will not be repeated here. Of course, in the process of obtaining isocyanate-modified chitosan, subsequent treatments such as cleaning and drying are also included to wash away the incompletely reacted chitosan, 1,6-hexamethylene diisocyanate and organic solvent from the reactants, thereby reducing the impurity content in the obtained isocyanate-modified chitosan. Of course, conventional cleaning agents such as acetone and butanone can be used for cleaning, which will not be repeated here.

[0024] The highly elastic and wrinkle-resistant microfiber sports shoe upper leather of the present application will be specifically described below.

[0025] like Figure 1 As shown, a highly elastic and wrinkle-resistant microfiber sports shoe upper comprises a base layer 1, a foaming layer 2 and a surface layer 3. The base layer 1 is a microfiber layer, the foaming layer 2 is a PU foaming layer, and the surface layer 3 is a mixture of at least two anionic water-based urethanes, an auxiliary agent, and a solvent water in a weight ratio of 1.8-2.2:0.05-0.5:5-7, which is then coated, pre-dried, and then attached to the outside of the PU foaming layer, and then subjected to load pressurization and curing. The auxiliary agent comprises a crosslinking agent and isocyanate-modified chitosan. The isocyanate-modified chitosan is obtained by crosslinking 1,6-hexamethylene diisocyanate with chitosan.

[0026] It should be noted that during the pre-drying process, the drying degree is controlled to 40-60%, and during the load pressurization process, the pressure is controlled to 6-22 kg / cm 2 .

[0027] The curing molding can be either thermal curing or UV curing, which will not be described in detail here.

[0028] In order to improve the elasticity and comfort of the high-elastic wrinkle-resistant microfiber sports shoe upper leather of this application, the microfiber layer is a water-soluble polyester and polyester or polyamide sea island fiber cloth. The PU foam layer is composed of water-based foaming resin, copper chloride, sodium alginate in a weight ratio of 100:4-6:0.1-0.5 and hollow glass microspheres with a mass percentage of 0.85-1.12%, and the PU foam layer is obtained by mixing, coating and drying. Among them, the water-based foaming resin in the embodiment of this application is an anionic aliphatic polyether polyurethane dispersion purchased from Wanhua Chemical. 1630B.

[0029] In the embodiment of the present application, the crosslinking agent is alkoxy melamine, and the embodiment of the present application adopts methoxy melamine, ethoxy melamine or butoxy melamine. Of course, any other alkoxy melamine has the possibility of being used as a crosslinking agent, which will not be described here. The mass ratio of the crosslinking agent to the anionic water-based urethane is 0.03-0.4:1.8-2.2.

[0030] The preparation steps of isocyanate-modified chitosan include: ① dissolving chitosan in an organic solvent to obtain a chitosan solution with a concentration of not less than 0.2 g / ml; ② adding 1,6-hexamethylene diisocyanate solution to the chitosan solution, controlling the molar ratio of 1,6-hexamethylene diisocyanate to chitosan to be 1:4-6, and adding a catalyst to stir to obtain a mixture; ③ placing the mixture in a water bath controlled at a temperature of 50-75°C and stirring and refluxing for 2-12 hours to obtain isocyanate-modified chitosan.

[0031] It should be mentioned that the catalyst is an organic tin catalyst, and the catalyst used in this application is dibutyltin dilaurate. Of course, other organic tin catalysts are also possible to be used as catalysts, which will not be described in detail here.

[0032] In the embodiments of the present application, the two anionic water-based urethanes used include COADD SC-2D-400 acrylic acid-modified anionic water-based urethane oil purchased from Qieke New Material Technology (Shanghai) Co., Ltd. and water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd. in a mass ratio of 1:0.8-1.2.

[0033] Embodiment 1

[0034] like Figure 1 As shown, a highly elastic and wrinkle-resistant microfiber sports shoe upper comprises a base layer 1, a foaming layer 2 and a surface layer 3. The base layer 1 is a microfiber layer, the foaming layer 2 is a PU foaming layer, and the surface layer 3 is a mixture of at least two anionic water-based urethanes, an auxiliary agent and a solvent water in a weight ratio of 1.8:0.05:5, which is then coated, pre-dried, and then attached to the outside of the PU foaming layer, and then subjected to load pressurization and thermal curing. The auxiliary agent comprises a crosslinking agent and isocyanate-modified chitosan. The isocyanate-modified chitosan is obtained by crosslinking 1,6-hexamethylene diisocyanate with chitosan.

[0035] It should be noted that during the pre-drying process, the drying degree was controlled to 40%, and during the load pressurization process, the pressure was controlled to 6 kg / cm 2 .

[0036] In order to improve the elasticity and comfort of the high-elastic wrinkle-resistant microfiber sports shoe upper leather of the present application, the microfiber layer is a water-soluble polyester and a polyester sea-island fiber cloth. The PU foam layer is composed of anionic aliphatic polyether polyurethane dispersion, copper chloride, sodium alginate in a weight ratio of 100:4:0.1 and hollow glass microspheres with a mass percentage of 0.85%, and the PU foam layer is obtained by mixing, coating and drying.

[0037] In the first embodiment of the present application, the crosslinking agent is methoxy melamine, and the mass ratio of methoxy melamine to anionic water-based urethane is 0.03:1.8.

[0038] The preparation steps of isocyanate-modified chitosan include: ① dissolving chitosan in an organic solvent to obtain a chitosan solution with a concentration of 0.2 g / ml; ② adding 1,6-hexamethylene diisocyanate solution to the chitosan solution, controlling the molar ratio of 1,6-hexamethylene diisocyanate to chitosan to be 1:4, and adding dibutyltin dilaurate to stir to obtain a mixture; ③ placing the mixture in a water bath controlled at a temperature of 50° C. and stirring and reflux for 2 hours to obtain isocyanate-modified chitosan.

[0039] In Example 1 of the present application, the two anionic water-based urethanes used include COADD SC-2D-400 acrylic acid-modified anionic water-based urethane oil purchased from Qieke New Material Technology (Shanghai) Co., Ltd. and water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd. in a mass ratio of 1:0.8.

[0040] Embodiment 2

[0041] like Figure 1 As shown, a highly elastic and wrinkle-resistant microfiber upper for sports shoes comprises a base layer 1, a foaming layer 2 and a surface layer 3. The base layer 1 is a microfiber layer, the foaming layer 2 is a PU foaming layer, and the surface layer 3 is a mixture of at least two anionic water-based urethanes, an auxiliary agent and a solvent water in a weight ratio of 2:0.2:6, which is then coated, pre-dried, and then attached to the outside of the PU foaming layer, and then subjected to load pressurization and thermal curing. The auxiliary agent comprises a crosslinking agent and isocyanate-modified chitosan. The isocyanate-modified chitosan is obtained by crosslinking 1,6-hexamethylene diisocyanate with chitosan.

[0042] It should be noted that during the pre-drying process, the drying degree was controlled to 50%, and during the load pressurization process, the pressure was controlled to 15 kg / cm 2 .

[0043] In order to improve the elasticity and comfort of the high-elastic wrinkle-resistant microfiber sports shoe upper leather of this application, the microfiber layer is a water-soluble polyester and a polyester sea-island fiber cloth. The PU foam layer is composed of a water-based foaming resin, copper chloride, sodium alginate in a weight ratio of 100:5:0.3 and 1.01% hollow glass microspheres, and the PU foam layer is obtained by mixing, coating and drying. Among them, the water-based foaming resin in the embodiment of this application is an anionic aliphatic polyether polyurethane dispersion purchased from Wanhua Chemical. 1630B.

[0044] In the embodiment of the present application, the crosslinking agent is ethoxy melamine, and the mass ratio of the crosslinking agent to the anionic water-based urethane is 0.2:2.

[0045] The preparation steps of isocyanate-modified chitosan include: ① dissolving chitosan in an organic solvent to obtain a chitosan solution with a concentration of not less than 0.2 g / ml; ② adding 1,6-hexamethylene diisocyanate solution to the chitosan solution, controlling the molar ratio of 1,6-hexamethylene diisocyanate to chitosan to be 1:5, and adding dibutyltin dilaurate to stir to obtain a mixture; ③ placing the mixture in a water bath controlled at a temperature of 60° C. and stirring and reflux for 6 hours to obtain isocyanate-modified chitosan.

[0046] In the embodiments of the present application, the two anionic water-based urethanes used include COADD SC-2D-400 acrylic acid-modified anionic water-based urethane oil purchased from Qieke New Material Technology (Shanghai) Co., Ltd. and water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd. in a mass ratio of 1:1.

[0047] Embodiment 3

[0048] like Figure 1 As shown, a highly elastic and wrinkle-resistant microfiber upper for sports shoes comprises a base layer 1, a foaming layer 2 and a surface layer 3. The base layer 1 is a microfiber layer, the foaming layer 2 is a PU foaming layer, and the surface layer 3 is a mixture of at least two anionic water-based urethanes, an auxiliary agent, and a solvent water in a weight ratio of 2.2:0.5:7, which is then coated, pre-dried, and then attached to the outside of the PU foaming layer, and then subjected to load pressurization and thermal curing. The auxiliary agent comprises a crosslinking agent and isocyanate-modified chitosan. The isocyanate-modified chitosan is obtained by crosslinking 1,6-hexamethylene diisocyanate with chitosan.

[0049] It should be noted that during the pre-drying process, the drying degree was controlled to 60%, and during the load pressurization process, the pressure was controlled to 22 kg / cm 2 .

[0050] In order to improve the elasticity and comfort of the high-elastic wrinkle-resistant microfiber sports shoe upper leather of this application, the microfiber layer is a water-soluble polyester and a polyester sea-island fiber cloth. The PU foam layer is composed of a water-based foaming resin, copper chloride, sodium alginate in a weight ratio of 100:6:0.5 and 1.12% of hollow glass microspheres, and the PU foam layer is obtained by mixing, coating and drying. Among them, the water-based foaming resin in the embodiment of this application is an anionic aliphatic polyether polyurethane dispersion purchased from Wanhua Chemical. 1630B.

[0051] In the embodiment of the present application, the crosslinking agent is butoxy melamine, and the mass ratio of the crosslinking agent to the anionic water-based urethane is 0.4:2.2.

[0052] The preparation steps of isocyanate-modified chitosan include: ① dissolving chitosan in an organic solvent to obtain a chitosan solution with a concentration of not less than 0.2 g / ml; ② adding 1,6-hexamethylene diisocyanate solution to the chitosan solution, controlling the molar ratio of 1,6-hexamethylene diisocyanate to chitosan to be 1:6, and adding dibutyltin dilaurate to stir to obtain a mixture; ③ placing the mixture in a water bath controlled at a temperature of 75° C. and stirring and refluxing for 12 hours to obtain isocyanate-modified chitosan.

[0053] In the embodiments of the present application, the two anionic water-based urethanes used include COADD SC-2D-400 acrylic acid-modified anionic water-based urethane oil purchased from Qieke New Material Technology (Shanghai) Co., Ltd. and water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd. in a mass ratio of 1:1.2.

[0054] Comparative Example 1

[0055] The difference between Comparative Example 1 and Example 2 is that no isocyanate-modified chitosan is added in Comparative Example 1.

[0056] Comparative Example 2

[0057] The difference between Comparative Example 2 and Example 2 is that sodium alginate is not added in Comparative Example 2.

[0058] Comparative Example 3

[0059] The difference between Comparative Example 3 and Example 2 is that calcium carbonate is used instead of copper chloride in Comparative Example 3.

[0060] Comparative Example 4

[0061] The difference between Comparative Example 4 and Comparative Example 1 is that Comparative Example 4 contains only one anionic water-based urethane, and the anionic water-based urethane is water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd.

[0062] Performance Test:

[0063] Performance tests were conducted on the above Examples 1 to 3 and Comparative Examples 1 to 4, and the thickness of the surface layer 3 was controlled to be 0.03 mm, the thickness of the foaming layer 2 was controlled to be 0.25 mm, and the thickness of the base layer 1 was controlled to be 1.2 mm.

[0064] 1. Use GT-303 leather softness tester to test the softness;

[0065] 2. Use synthetic leather peel strength tester to perform peel strength test;

[0066] 3. Use QB / T2717-2005 to test the folding fastness.

[0067] The performance test results are shown in Table 1 below.

[0068] Table 1 Performance test results

[0069]

[0070]

[0071] From Table 1 above, it can be seen that the use of sodium alginate in the embodiment of the present application improves the viscosity, and enables the hollow glass microspheres to be foamed into holes, while keeping the holes evenly distributed and reducing the pore size difference during the molding process, will solve the problem of reduced softness. Based on this, the embodiment of the present application combines hollow glass microspheres with cupric chloride and a variety of anionic water-based urethanes to improve softness, so that it can maintain a moderate softness during use.

[0072] At the same time, when isocyanate-modified chitosan is not added, the peel strength of the obtained high-elasticity and wrinkle-resistant microfiber sports shoe upper leather will be significantly affected, and when sodium alginate is not added or calcium carbonate is used instead of copper chloride, the peel strength of the obtained high-elasticity and wrinkle-resistant microfiber sports shoe upper leather will be less adversely affected.

[0073] The present application provides a highly elastic and wrinkle-resistant microfiber sports shoe upper leather, which forms a network structure by isocyanate-modified chitosan, and cooperates with at least two anionic water-based urethanes to form a densely structured cross-linked three-dimensional structure with a cross-linking agent, thereby reducing the hydrophilicity of the surface layer while achieving the effect of improving acid resistance and thermal stability, and the overall structure has high strength and good elasticity to achieve the purpose of wrinkle resistance. For the base layer 1, it has good elastic tensile strength, and through the improvement of the hydrophobicity of the surface layer, the purpose of effective waterproofing is achieved, and after testing, the water resistance meets the requirements of at least 1.5 minutes based on a pressure of 14.7 kPa.

[0074] Among them, after the composite film of at least two anionic water-based urethanes and the crosslinking agent and the isocyanate-modified chitosan is formed, the structural strength of the surface is significantly improved while reducing the loss of elasticity of the surface layer, and at the same time has the effect of improving thermal stability and acid resistance;

[0075] At the same time, the viscosity of the PU foaming layer is improved by sodium alginate, and the hollow glass microspheres are foamed into holes, while the holes are kept evenly distributed and the pore size differences are reduced during the molding process. Cupric chloride is fully dispersed in the PU foaming layer as an inorganic filler. While improving the strength of the PU foaming layer, it also improves the bonding strength with the surface layer, achieves antibacterial effects, and improves the peeling strength of the high-elasticity and wrinkle-resistant microfiber sports shoe upper leather.

[0076] The "first", "second", "third", "fourth", etc. (if any) referred to in this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, or devices.

[0077] It should be noted that the descriptions involving "first", "second", etc. in this application are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0078] Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A highly elastic and wrinkle-resistant microfiber sports shoe upper leather, characterized in that: The invention comprises a base layer, a foaming layer and a surface layer; the base layer is a superfine fiber layer, the foaming layer is a PU foaming layer, the surface layer is prepared by mixing at least two anionic water-based urethanes with an auxiliary agent and a solvent water in a weight ratio of 1.8-2.2:0.05-0.5:5-7, and then coating and pre-drying are performed, and then the mixture is attached to the outer side of the PU foaming layer, and then subjected to load, pressurization and curing to form; the auxiliary agent comprises a crosslinking agent and isocyanate-modified chitosan; the isocyanate-modified chitosan is obtained by crosslinking reaction between 1,6-hexamethylene diisocyanate and chitosan.

2. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 1, characterized in that: The cross-linking agent is methoxy melamine, ethoxy melamine or butoxy melamine, and the mass ratio of the cross-linking agent to the anionic water-based urethane is 0.03-0.4:1.8-2.

2.

3. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 1, characterized in that: The preparation steps of the isocyanate-modified chitosan include: ① dissolving chitosan in an organic solvent to obtain a chitosan solution with a concentration of not less than 0.2 g / ml; ② adding a 1,6-hexamethylene diisocyanate solution to the chitosan solution, controlling the molar ratio of 1,6-hexamethylene diisocyanate to chitosan to be 1:4-6, and adding a catalyst to stir to obtain a mixture; ③ placing the mixture in a water bath for stirring and reflux treatment to obtain the isocyanate-modified chitosan.

4. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 3, characterized in that: The temperature of the water bath is controlled at 50-75° C., and the reflux treatment is performed for 2-12 hours.

5. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 3, characterized in that: The catalyst is dibutyltin dilaurate.

6. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 1, characterized in that: The two anionic water-based urethanes include COADD SC-2 D-400 acrylic acid-modified anionic water-based urethane oil purchased from Qieke New Material Technology (Shanghai) Co., Ltd. and water-based polyurethane resin 2877 purchased from Shanghai Yuanhe Chemical Co., Ltd. in a mass ratio of 1:0.8-1.

2.

7. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 1, characterized in that: The pre-drying is to control the drying degree to 40-60%, and the load pressurization is to control the pressure to 6-22kg / cm 2 , and the curing molding is thermal curing or UV curing.

8. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 1, characterized in that: The ultrafine fiber layer is water-soluble polyester and polyester or polyamide sea island fiber cloth.

9. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 1, characterized in that: The PU foam layer is composed of water-based foaming resin, copper chloride, sodium alginate in a weight ratio of 100:4-6:0.1-0.5 and hollow glass microspheres in a mass percentage of 0.85-1.12%, and the PU foam layer is obtained by mixing, coating and drying.

10. The high-elastic and wrinkle-resistant microfiber sports shoe upper leather according to claim 9, characterized in that: The water-based foaming resin is an anionic aliphatic polyether polyurethane dispersion, which is purchased from Wanhua Chemical's Adwel® 1630B.

Citation Information

Patent Citations

  • Superfine fiber synthetic leather and processing method thereof

    CN118653303A